Training on the Preparation of Simple Financial Statements for Mosque /Mushollah and Youth Organizations of Mosque in the Kerinjing Village - Yusnaini Yusnaini; Burhanudin Burhanudin; Nur Khamisah (Sricommerce: Journal of Sriwijaya Community Services, 2021)
This Community Service Activity aims to train the Management (Ta'mir) and youth of mosques at the mosque in Kerinjing Village to (a) understand the importance of financial statements as a form of responsibility for the mandate they carry out, and (b) understand the importance of Standard financial statements in order to provide more macro benefits, and (c) practice compiling mosque financial statements in accordance with generally accepted regulations by utilizing information technology. The method applied is training through workshops within a certain time. The workshop will provide 3 main materials, namely: (1) understanding the importance of financial reporting in accountability, transparency and good governance; (2) training in manual preparation of mosque financial statements; and (3) training on the preparation of mosque financial statements using information technology, namely by using Microsoft Excel. After attending the workshop, it is expected that there will be a better understanding of the Management (Ta'mir) and youth of mosque on the importance of preparing mosque financial statements and at the same time having adequate competence to compile periodic financial statements, namely monthly, quarterly, semester and annually.